Antidepressant use and risk of adverse outcomes in people aged 20–64 years: cohort study using a primary care database - Coupland, Carol; Hill, Trevor; Morriss, Richard; Moore, Michael; Arthur, Antony; Hippisley-Cox, Julia (BioMed Central, 2018)
Background: Antidepressants are one of the most commonly prescribed medications in young and middle-aged adults, but there is relatively little information on their safety across a range of adverse outcomes in this age group. This study aimed to assess associations between antidepressant treatment and several adverse outcomes in people aged 20–64 years diagnosed with depression.